The CD68+ macrophages to CD8+ T-cell ratio is associated with clinical outcomes in hepatitis B virus (HBV)-related hepatocellular carcinoma. Issue 7 (July 2021) - Xin, Haibei; Liang, Dandan; Zhang, Minfeng; Ren, Dandan; Chen, Huan; Zhang, Hao; Li, Shanshan; Ding, Guanghui; Zhang, Cunzhen; Ding, Zhiwen; Wu, Lihong; Han, Wenbo; et al.
Abstract: Background: Tumor microenvironment plays an essential role during the progression of hepatocellular carcinoma (HCC). Tumor infiltrating immune cells (TILs) was an important component of tumor microenvironment. However, whether TIL features are correlated with the prognosis of HCC patients remains unclear. Methods: Cancer tissue and paired paracancerous tissues from 220 stage II∼III HBV-related HCC patients were collected. TILs were analyzed using a tyramide signal amplification system combined with immunohistochemistry. Kaplan-Meier survival analysis was conducted to investigate the associations between the prognosis and the infiltrating pattern of TILs. Results: The patients were classified into three distinct subgroups (Clusters (C)1–3) with different overall survival (OS) and disease-free survival (DFS) according to the distribution pattern of TILs. The CD68/CD8 ratio in the cancer SA was correlated with the prognosis. Patients with a higher CD68/CD8 ratio exhibited poorer OS and DFS than those with a lower ratio. The CD68/CD8 ratio in the cancer SA was an independent factor for OS prediction but not DFS. Conclusion: CD68+ macrophages and CD8+ T-cells are essential immunological determinants for HBV-related HCC prognosis, and the CD68/CD8 ratio in cancer SA is a novel, prognostic factor for OS prediction in HBV-related HCC patients.